ANALISIS PENGARUH PENGALAMAN KERJA, PENDIDIKAN SERTA KOMPENSASI TERHADAP KINERJA BADAN AD HOC DI BAWASLU DEMAK - Suprihono Setyawan; Muhammad Syaqiq (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This study aims to find out how much influence the factors of work experience, education and compensation on the performance of the Ad hoc Agency in Bawaslu Demak Regency, with the target being the Ad hoc committee at the sub-district level and the village/sub-district level in Demak Regency with a total of 294 people. This research uses a collaborative or combined method, which is combining qualitative methods with quantitative methods with the aim of obtaining more valid answers that will be able to explain the research problem.. From the results of the test, it can be concluded that all the variables studied have a positive effect on the performance of the Ad Hoc Body. There are several important notes that need to be paid attention to by the Demak Regency Bawaslu, that the lowest indicator states that actually the Ad hoc committee is of the opinion that the honorarium they receive needs to be increased. Then there is an indicator that has the greatest value, namely that all Ad hoc committees are of the opinion that training/technical guidance must be carried out frequently by the Demak Regency Bawaslu.